"On Nomadic Shores Inward": Harry Martinson's Journey to Late-Life Suicide. (28th January 2021) - Titelman, David
Abstract : The aim of this study was to explore the unconscious dimensions of suicide as conveyed by the Swedish writer Harry Martinson, who took his life in 1978, four years after having received the Nobel Prize in Literature. A psychoanalytically informed "listening" to Martinson comprised a close reading of his writings, reflection on my total response to the material, the application of psychoanalytic hypotheses on severe depression and suicide-nearness, and the study of biographical sources. The dramatic fluctuations of Martinson's self-regard were noted, as was the juxtaposition of opposites in his poetry: darkness that seeps through observations of the beauty of nature and man or the reverse, a gleam of love that defuses the cruelty of the world. Martinson's drive to communicate with himself and others by talking and writing, to find auxiliary objects compensating for the traumatic losses of his childhood, and to realize mature love in adulthood was understood as a counterforce to self-destructiveness and threatening narcissistic disintegration. Pressured by negative reactions to the Nobel, which overlay decades of envy and political critique from colleagues, whose support he coveted, Martinson's aggressivity—reflecting the near soul-murder of his early life—exploded in his suicide.